Construction and Validation of a Compassionate Nursing Care Scale from the Perspective of the Patient-Family Caregiver Dyad - Archila Hernández, Edwin Darío; Torres Acosta, Doris Helena; Pulido Barragán , Sandra Patricia; Laverde Contreras, Olga Lucía; Sánchez Herrera, Beatriz (Investigación y Educación en Enfermería, 2024)
Objective. This work sought to determine the composition, comprehensibility, face validity, and content validity of the Compassionate Care Scale “HUS-CC”, to assess the perception of the patient-family caregiver dyad on the compassionate nursing care they receive in hospital services. Methods. Methodological research conducted in a hospital network with services at different levels of complexity in Colombia. To evaluate the comprehensibility of the HUS-CC, 204 individuals participated. The face and content validity were valued by 17 experts and ratified with 213 dyads. An exploratory factor analysis with varimax rotation was conducted and reliability was calculated with Cronbach’s alpha. Results. The scale was clear and understandable. Its face and content validity index were 0.77; the Fleiss Kappa index was 0.59 and Aiken’s V was 0.9; with Cronbach’s alpha of 0.84. The HUS-CC has 16 items grouped into three dimensions: warm treatment, inclusive attitude, and supportive behavior. Conclusion. The HUS-CC scale proved valid to evaluate the perception of patient-family caregiver dyads about compassionate nursing care in hospital services.